Bioactive peptides from Sacha Inchi (Plukenetia volubilis) cake: Extraction techniques and their antioxidant, antihypertensive, hypoglycemic, and iron-chelating potential through in vitro and in silico analysis - Chirinos, Rosana; Figueroa-Merma, Andres; Valente de Oliveira, Thomas; Guzmán, Fanny; Aguilar-Galvez, Ana; Carpentier, Sebastien; Pedreschi, Romina; Campos, David (Elsevier BV, 2025)
This study evaluated the multifunctional properties of hydrolysates from Sacha Inchi (SI) protein extracted through conventional (SICPH) and ultrasound-assisted extraction (SIUSPH). Additionally, peptides were identified via LC-MS/MS following ultrafiltration and size exclusion chromatography (SEC), with the study concluding in peptide synthesis. The functional properties of the hydrolysates and peptides were assessed using both in vitro and in silico techniques. SICPH and SIUSPH exhibited antioxidant properties, iron (Fe+2) chelation, antihypertensive and hypoglycemic activities. From the ultrafiltered hydrolysates and passed through SEC, a total of 8 novel SI peptides (CPNF, FLY, LMW, PCW, WPL, WMPY, DPGGW, and NWPF) were identified, with structural differences depending on the extraction method employed. The synthesized peptides exhibited distinct bioactive properties: PCW showed notable antihypertensive activity (ACE inhibitory concentration, IC₅₀ = 16 µg/mL); NWPF displayed hypoglycemic potential (DPP-IV inhibitory concentration, IC₅₀ = 0.64 mg/mL); CPNF demonstrated iron-chelating capacity (0.209 µg Fe²⁺/mg); and FLY exhibited strong antioxidant activity, with ORAC and ABTS values of 5.14 and 7.45 µmol TE/mg, respectively. In silico molecular docking studies confirmed the inhibition of ACE and DPP IV enzymes, and ADMET analysis indicated that most peptides had favorable pharmacokinetic properties with no signs of toxicity. Thus, SI protein cake represents a valuable source for producing multifunctional protein hydrolysates and biopeptides.